Pregestational body mass index is related to neonatal abdominal circumference at birth—a Danish population‐based study. Issue 3 (12th November 2012) - Tanvig, M; Wehberg, S; Vinter, CA; Joergensen, JS; Ovesen, PG; Beck‐Nielsen, H; Jensen, DM; Christesen, HT
Abstract : Objectives: To examine the impact of maternal pregestational body mass index (BMI) and smoking on neonatal abdominal circumference (AC) and weight at birth. To define reference curves for birth AC and weight in offspring of healthy, nonsmoking, normal weight women. Design: Population‐based study. Setting: Data from the Danish Medical Birth Registry. Population: All live singletons without congenital malformations in Denmark 2004–10. Methods: Data on 366 886 singletons at 35 +0 to 41 +6 weeks +days of gestation were extracted and analysed using multivariate linear regressions. Main outcome measures: Birth AC and weight in relation to pregestational maternal BMI, maternal smoking and medical conditions (any). Results: Birth AC and weight increased with increasing pregestational BMI, and decreased with smoking ( P < 0.0001). Reference curves were created for offspring of healthy, nonsmoking mothers with normal pregestational BMI. Mean AC ranged from 30.1 cm and 30.2 cm at 35 weeks of gestation to 33.9 cm and 34.1 cm at 41 weeks of gestation, for girls and boys, respectively. Mean birthweight ranged from 2581 and 2666 g at 35 weeks to 3705 and 3852 g at 41 weeks of gestation for girls and boys, respectively. Pregestational BMI correlated more to the Z score of birthweight than to the Z score of AC ( P < 0.0001). Conclusion: Birth AC and weight are affected by maternal smoking status and pregestational BMI. Pregestational BMI correlated more to birthweight than to AC. Using data from healthy, nonsmoking mothers with normal pregestational BMI we have provided new reference curves for birth AC and birthweight.